2022
DOI: 10.3390/biom12111565
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on the Role of Natural Products in Overcoming Cancer Drug Resistance: An Autophagy-Based Perspective

Abstract: Autophagy is a critical cellular adaptive response in tumor formation. Nutritional deficiency and hypoxia exacerbate autophagic flux in established malignancies, promoting tumor cell proliferation, migration, metastasis, and resistance to therapeutic interventions. Pro-survival autophagy inhibition may be a promising treatment option for advanced cancer. Furthermore, excessive or persistent autophagy is cytotoxic, resulting in tumor cell death. Targeted autophagy activation has also shown significant promise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 157 publications
(196 reference statements)
0
4
0
Order By: Relevance
“…In the second case, the cell has a chance to clean up and survive if the damage to the organelles is relatively limited. An important research area in modern oncology is the inhibition of the autophagy mechanism and the initiation of apoptosis [ 44 , 45 ]. Some studies on acute myeloid leukaemia, however, suggest that cancer cell differentiation is stimulated through the initiation of autophagy [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the second case, the cell has a chance to clean up and survive if the damage to the organelles is relatively limited. An important research area in modern oncology is the inhibition of the autophagy mechanism and the initiation of apoptosis [ 44 , 45 ]. Some studies on acute myeloid leukaemia, however, suggest that cancer cell differentiation is stimulated through the initiation of autophagy [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al found that the level of the miR-27a expression was obviously elevated under hypoxia and improved paclitaxel resistance by restricting the expression of APAF1 . Cell autophagy is a highly conserved biological process that breaks down and reuses long-lived organelles or damaged, misfolded proteins, which can lower cancer cell susceptibility to therapeutic reagents in various types of human cancer and be induced in solid hypoxia tumors and play a prosurvival role . Hypoxia-induced autophagy increases tumor cell lifetime, promotes a more destructive phenotype, and increases the risk of metastasis.…”
Section: Hypoxia-induced Impediments In Tumor Treatmentmentioning
confidence: 99%
“…113 Cell autophagy is a highly conserved biological process that breaks down and reuses long-lived organelles or damaged, misfolded proteins, which can lower cancer cell susceptibility to therapeutic reagents in various types of human cancer and be induced in solid hypoxia tumors and play a prosurvival role. 114 Hypoxia-induced autophagy increases tumor cell lifetime, promotes a more destructive phenotype, and increases the risk of metastasis. In addition, hypoxia-induced autophagy increases tumor cell resistance to cancer therapy.…”
Section: Hypoxia-induced Impediments In Tumor Treatmentmentioning
confidence: 99%
“…Autophagy is regarded as an adaption way for tumor cells to survival along with long time evolution. Herein, it has been certified to play a double-edged sword in drug resistance ( Smith and Macleod, 2019 ; Yao et al, 2022 ). On one hand, autophagy participates in the development of drug resistance and protects cancer cells from chemotherapeutics ( Gao et al, 2022 ).…”
Section: Resistance Mechanismmentioning
confidence: 99%